البنوك التجارية و تحديات التجارة الالكترونية - بن دودو الندير; ميدون عبد الرحمن; بوداود فاطمة الزهراء (جامعة عمار ثليجي الاغواط, 2022)
Our topic aims at commercial banks and the challenges of electronic commerce to know the role of the latter in improving the efficiency of electronic banking services, with a focus on analyzing their reality in the banking agency and the extent of their manifestations, and discussing the most prominent obstacles they face in applying their techniques. The study showed the critical importance of this information revolution, and its effects on improving electronic banking service mechanism. In order for banks to be able to adapt quickly to adopt electronic commerce and adopt it within their marketing policy in order to develop their products and introduce electronic technologies in them to suit the nature of this commerce, and promote them according to modern electronic methods that are rapidly spreading, in this case they will find themselves in competition, which preserves their share market and competitive position. In this study, we will try to monitor the most important practices and determine the impact of electronic commerce on commercial banks, which have new practices of interest, especially in the field of electronic banking services, and that they are the most involved in modern technology. This study showed that there is an effect and a link between electronic commerce and electronic banking services in the banking agency of commercial banks. From here emerges the role played by the newly developed electronic payment methods through electronic money transfer.